Cross-country evidence on project portfolio success in the Asia-Pacific region: Role of CEO transformational leadership, portfolio governance and strategic innovation orientation - Umer Zaman; Raja Danish Nadeem; Shahid Nawaz (Cogent Business & Management, 2020)
Project portfolio management ensures a hierarchy of purpose and effective prioritization of projects in achieving organization's strategic objectives. This study argues that the lack of discipline in integrating projects makes project portfolio investments and anticipated benefits unclear, causing internal congestion of indecisive and/or unsuccessful projects. This research empirically scrutinizes project portfolio success in a transnational and cross-cultural perspective in the Asia-Pacific (APAC) region. Based on samples drawn from the information and communications technology (ICT) industry in the Republic of Korea (an advanced economy) and Pakistan (an emerging economy), the hypothesized relationships were empirically tested using partial least squares structural equation modeling (PLS-SEM). The study findings revealed a significant and positive effect of CEO transformational leadership on project portfolio success. The findings also confirmed that strategic innovation orientation significantly mediates the effect of CEO transformational leadership on project portfolio success. In addition, this study provides support for portfolio governance mechanism in a moderating role that significantly enhanced the relationships between CEO transformational leadership and project portfolio success; also, strategic innovation orientation and project portfolio success. This study presents convergent views between Korea (Study-I) and Pakistan (Study-II) in terms of the application of CEO transformational leadership, portfolio governance and strategic innovation in explaining project portfolio success. Implications of findings are drawn based on a new perspective of project portfolio success in a cross-country context.
Keywords: 650; Transformational leadership; portfolio governance; strategic innovation orientation and project portfolio success